(untitled) - Wright, John S. (New York, 1966)
Moriarty teaches students about effective marketing. The text covers the foundations of advertising, planning and strategy, effective advertising media, creating effective messages, as well as integration and evaluation. For advertising professionals and business students concentrating in marketing or advertising.
Keywords: Advertising